The use of radiofrequency energy during arthroscopic surgery and its effects on intraarticular tissues - Horstman, C. L.; McLaughlin, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The use of radiofrequency (RF) energy has become very popular in human and veterinary arthroscopic surgery since the late 1990's. Both monopolar and bipolar RF units are available. Application of RF energy to joint capsular tissue leads to immediate tissue shrinkage that is both power and temperature dependent. Changes in joint capsular tissue have been noted at temperatures greater than 65°C. Treatment of articular cartilage with RF energy leads to immediate chondrocyte damage. This damage is also power and temperature dependent and is observed at temperatures as low as 45°C. Caution should be used when applying RF energy within a joint to prevent or minimize articular cartilage injury.
Keywords: Arthroscopy; radiofrequency; joint capsule; articular cartilage